Cyfrowa anemometria obrazowa (PIV) - budowa i testy stanowiska pomiarowego = Digital image anemometry (PIV) - construction and testing of the measuring set-up - Ochowiak, Marek; Włodarczak, Sylwia; Krupińska, Andżelika; Markowska, Małgorzata (Zielona Góra: Uniwersytet Zielonogórski, Instytut Metrologii, Elektroniki i Informatyki)
The article presents the basics of measuring method Particle Image Velocimetry (PIV), a non- intrusive technique for determining fluid velocity fields and the designed and constructed universal PIV digital anemometry set-up and its applicability. It can be widely used, both in industry and in scientific laboratory research.
Keywords: komputeryzacja; przyrządy pomiarowe; informatyka; technologie informacyjne